Analysis of the Presence and Impact of Price Gap Anomaly on the Indonesian Stock Exchange - Rinaldi Wilopo; Irwan Adi Ekaputra (Green Publisher Indonesia, 2025)
Price gap occurs when the opening price of a financial asset today is greater than the closing price of the previous day, signaling market’s initial sentiment and potential direction of price movement on the trading day. This study aims to explore the presence and characteristics of price gap anomalies and their potential exploitation to generate abnormal returns in the Indonesian stock market. The data used are 11 stock indices in the period 2015-2024 and the analysis is carried out using the multiple linear regression method to test the hypothesis. The results of the study indicate that price gap anomalies are confirmed in the Indonesian stock market, with positive price gaps tending to have more momentum effects than negative price gaps. Price gaps show short-term characteristics, where this anomaly does not affect the period after period of the anomaly. This study also explores the addition of volatility as a control variable in the regression model and finds the accuracy of the regression model by observing the increase in Adjusted R-Squared and Overall F-Test values. Finally, a trading strategy is formed to test the strategy's ability to generate abnormal returns that can beat the market in the Indonesian stock market. However, considering the transaction costs, the overall trading simulation results cannot generate returns that can beat market returns.